A C and D are incorrect. Only B is correct.
A take for example f= (x-c^2) + 1 The remainder is 1
C take f(x)= x+3/2. the remainder is 1
D take f(x)= (x^2-c)+1 the remainder is 1.
All the above are not correct
B is correct since f(x)- Ax^n+Bx^(n-1) + Cx^(n-2) +....Yx + Z. All terms devided by x except Z which is a constant and obviously f(0)=Z
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?